2020
DOI: 10.1155/2020/3279710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Living High-Training Low and High on Body Composition and Metabolic Risk Markers in Overweight and Obese Females

Abstract: This study examined the effects of 4 weeks of living high-training low and high (LHTLH) under moderate hypoxia on body weight, body composition, and metabolic risk markers of overweight and obese females. Nineteen healthy overweight or obese females participated in this study. Participants were assigned to the normoxic training group (NG) or the LHTLH group (HG). The NG participants lived and trained at sea level. The HG participants stayed for approximately 10 hours in a simulated 2300 m normobaric state of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Previous studies conducted by our group reported that Hypoxic Training is effective in regulating lipid metabolism in obese rats. The findings showed that the main mechanisms involve skeletal muscle fatty acid metabolism and liver lipid metabolism ( Lu et al, 2014 ; Lu et al, 2016 ; Gao et al, 2020 ). However, effect of Hypoxic exercise on BAIBA secretion in obese rats has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted by our group reported that Hypoxic Training is effective in regulating lipid metabolism in obese rats. The findings showed that the main mechanisms involve skeletal muscle fatty acid metabolism and liver lipid metabolism ( Lu et al, 2014 ; Lu et al, 2016 ; Gao et al, 2020 ). However, effect of Hypoxic exercise on BAIBA secretion in obese rats has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Similar changes were also reported after living at moderate altitudes (days-weeks), where a decrease in TC and LDL-C levels [59][60][61] and an increase in HDL-C levels [61] were observed. In a recent study by Gao et al [62], the authors did not find statistically significant changes in the lipid profile following a four-week LH-TL protocol at a simulated altitude of 2300 m. It should be noted that these studies were performed with nontrained individuals and those with obesity and metabolic syndrome. A study involving athletes was conducted by Pialoux et al [63].…”
Section: Discussionmentioning
confidence: 92%
“…The mechanisms associated with the improvement of HDL-C after LH-TL are also unclear. In a recent study, Gao et al [62] suggested that exposure to hypoxia may prevent the loss of HDL-C due to the increased expression of the lipoprotein lipase gene as a result of hypoxia-induced factor 1 (HIF1) upregulation. Furthermore, the activation of HIF1 may enhance HDL particle synthesis by stimulating the expression of ATP-binding cassette transporter ABCA1 [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…In formal exercise we used Polar meter to monitor heart rate, so as to control the intensity of exercise, target heart rate = resting heart rate + heart rate reserve × 20%–40% (heart rate reserve = maximum heart rate - resting heart rate). 20 Subjects in each group exercised five days a week, once a day, for 30 min each time, with 20 min of preparatory and finishing activities before and after exercise. 21 They did not carry out any form of exercise training except for the exercise required in the experiment.…”
Section: Methodsmentioning
confidence: 99%